RfpA, RfpB, and RfpC are the Master Control Elements of Far-Red Light Photoacclimation (FaRLiP) - Zhao, Chi; Gan, Fei; Shen, Gaozhong; Bryant, Donald A. (Frontiers in Microbiology, 2015)
Terrestrial cyanobacteria often occur in niches that are strongly enriched in far-red light (FRL; λ >700 nm). Some cyanobacteria exhibit a complex and extensive photoacclimation response, known as FRL photoacclimation (FaRLiP). During the FaRLiP response, specialized paralogous proteins replace 17 core subunits of the three major photosynthetic complexes: Photosystem (PS) I, PS II, and the phycobilisome. Additionally, the cells synthesize both chlorophyll (Chl f) and Chl d. Using biparental mating from Escherichia coli, we constructed null mutants of three genes, rfpA, rfpB, and rfpC, in the cyanobacteria Chlorogloeopsis fritschii PCC 9212 and Chroococcidiopsis thermalis PCC 7203. The resulting mutants were no longer able to modify their photosynthetic apparatus to absorb FRL, were no longer able to synthesize Chl f, inappropriately synthesized Chl d in white light, and were unable to transcribe genes of the FaRLiP gene cluster. We conclude that RfpA, RfpB, and RfpC constitute a FRL-activated signal transduction cascade that is the master control switch for the FaRLiP response. FRL is proposed to activate (or inactivate) the histidine kinase activity of RfpA, which leads to formation of the active state of RfpB, the key response regulator and transcription activator. RfpC may act as a phosphate shuttle between RfpA and RfpB. Our results show that reverse genetics via conjugation will be a powerful approach in detailed studies of the FaRLiP response.